Evaluation Study of Original McEliece Cryptosystem Against Side Channel Attack. - Abdulrazaq, Newroz N.; Qaradaghi, Thuraya M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Side channel attack is the most efficient attack against original McEliece cryptosystem, especially ball-collision and Bernstein et al.Stern attacks. The modified Stern attack hasan ability to break original McEliece cryptosystem with parameter [1024,524,101] in 1400 days with personal computers.While with 200 clusters CPU breaking could be done in 7 days. While ball-collision attacks have smallerexponent time than Stern algorithm.This paper will present a modified version of Patterson decoding algorithm using a new evaluation for finding error locations.This approach gave the sender an opportunity to choose errors less than identified errors in public key without notifying the receiver;therefore, it reduces the probability of modified Stern attack against McEliece cryptosystem to (0.02) and increases exponent time of ball-collision attack. In this paper alsothe leakage of proposed implementation has beenmeasured using a measurement type for possible leakage in Patterson’s decoding algorithm suggested by previous work, and we concluded that the designed system have fewer leakage compared to previous implementation. The workhas done using Visual Studio C#.
Keywords: McEliece Cryptosystem Side Channel Attack